2020
DOI: 10.3389/fpsyg.2020.00367
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Gender and Transgender Knowledge in University Students Through the Creative Factory Methodology

Abstract: In Spain, Social Educators, similar to both social workers and educators in the United States, help coordinate social change through educational interventions and mobilization of social groups to benefit marginalized people and overall societal welfare. They are trained to work with diverse populations, and it is important that they have awareness and training on gender and transgender issues given the extensive discrimination that transgender people endue. Research has begun to identify the important role tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
(51 reference statements)
1
12
0
1
Order By: Relevance
“…Other studies in Sweden, such as those of Landén and Innala [48], analysed the opinions of 668 persons drawn from the general population, focusing on the reassignment of sex and the rights of this group. Although in this study they found a majority were supportive of the rights of trans people, the least support was expressed for the payment of health care costs during sex-transition (with 63% opposed) and the right of transgender people to adopt and raise children (with 41% opposed) [43]. The limitation of this study was that an integrated instrument was not developed, because the constructs were evaluated separately reducing the capability to draw causal attributions.…”
Section: Contextual Considerations For the Evaluation Of Negative Attmentioning
confidence: 74%
See 3 more Smart Citations
“…Other studies in Sweden, such as those of Landén and Innala [48], analysed the opinions of 668 persons drawn from the general population, focusing on the reassignment of sex and the rights of this group. Although in this study they found a majority were supportive of the rights of trans people, the least support was expressed for the payment of health care costs during sex-transition (with 63% opposed) and the right of transgender people to adopt and raise children (with 41% opposed) [43]. The limitation of this study was that an integrated instrument was not developed, because the constructs were evaluated separately reducing the capability to draw causal attributions.…”
Section: Contextual Considerations For the Evaluation Of Negative Attmentioning
confidence: 74%
“…As verified by the educational level of the family members, low training is also closely related to negative attitudes towards trans people. This indicates the importance of detecting negative attitudes in other areas such as in the family, at work or in the community in general [43,44]. Therefore, the understanding and detection of these attitudes is crucial to generating interventions appropriate to the context and to promoting gender formations that include trans people in all areas and initiating the change in the education sector that will allow the transfer to the rest of the environments [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey was designed to be as unbiassed as possible, recognizing the logistical limitations throughout the process, the results present convincing tendencies and suggestions that should be considered when developing strategies that affect the experiences of LGBTQIA+ students [47].…”
Section: Methodsmentioning
confidence: 97%